2022
DOI: 10.1007/s00228-022-03438-4
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility analysis of a structured medication review compared to usual care in Parkinson’s disease

Abstract: Purpose For controlling symptoms in Parkinson's disease (PD) together with treating additional comorbidities, patients often face complex medication regimens, with suboptimal adherence, drug-related problems, and diminished therapy efficacy as a common consequence. A medication review could potentially tackle these issues, among others by optimizing drug treatment. Even if no change in clinical outcomes is observed, this intervention might decrease health care costs by reducing drug-related problems and hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“… 19 In our quantitative Medication Review in PD study, executed in accordance with the Dutch Medication Review guidelines at that time, we found no improvement in quality of life in PD patients after an SMR and higher expenditure of health care costs compared to usual care. 9 , 12 , 33 The explanation for these outcomes seems multifactorial. The merely mild disease severity, the primary care setting, the difficult multidisciplinary communication lines, patient characteristics or any combination might play a role.…”
Section: Discussionmentioning
confidence: 99%
“… 19 In our quantitative Medication Review in PD study, executed in accordance with the Dutch Medication Review guidelines at that time, we found no improvement in quality of life in PD patients after an SMR and higher expenditure of health care costs compared to usual care. 9 , 12 , 33 The explanation for these outcomes seems multifactorial. The merely mild disease severity, the primary care setting, the difficult multidisciplinary communication lines, patient characteristics or any combination might play a role.…”
Section: Discussionmentioning
confidence: 99%